Moderasi Beragama sebagai Proyek Intelektual: Telaah Konseptual atas Rekonstruksi Islam Modern Nurcholish Madjid - Fresyam Antika Ajeng (PT. Panca Publishing Indonesia, 2026)
This article examines religious moderation as an intellectual project within the framework of Islamic modernist reconstruction developed by Nurcholish Madjid. In response to the rise of religious radicalism rooted in textual literalism and symbolic formalism in Indonesia, this study repositions religious moderation not merely as a normative agenda or state policy, but as an epistemological consequence of Islamic neo-modernism. Employing a qualitative library research approach, the study analyzes Madjid’s primary works alongside recent scholarly literature on neo-modernism, religious moderation, and radicalism. The findings demonstrate that Madjid’s reconstruction of modern Islam is grounded in the integration of revelation and reason, contextual interpretation of Islamic teachings, and the prioritization of substantive moral values over symbolic formalism. This paradigm generates an inclusive, rational, and democracy-compatible religious orientation. Religious moderation, from this perspective, emerges as a methodological transformation in interpreting religious texts and tradition, functioning as a counter-epistemology to radicalism. The study argues that Islamic neo-modernism provides a robust theoretical foundation for strengthening religious moderation in contemporary Indonesia.